Las tensiones en el desarrollo motriz grueso de los niños y niñas de educación inicial II, subnivel 1 de 3 a 4 años, de la Unidad Educativa 11 de Noviembre, del sector urbano del cantón Latacunga - Toaquiza Yupangui, Fanny Elizabeth (2017)
As students of the Cotopaxi Technical University, Prescool Major, the research is presented whose main purpose was to establish the way in which the tensions in the gross motor development of children from 3 to 4 years, Stage II Sub-level I of 11 de Noviembre Educative Unit from Cotopaxi Province, Latacunga Canton, Ignacio Flores Parish in 2015-2016 academic year. It was significant to work on this thematic taking into account that in the current times has detected the remarkable loss of creativity at the time of playing as a consequence of an accelerated and at the same time sedentary life where infants have become sedentary beings that do not prioritize Human relations with their contemporaries spending most of their free time in front of the computer, electronic and video games. As the final product of the work, concluding on the problematic raised is to contribute to the integral development of children so that do not miss the fun of traditional games that allow them to develop their imagination by enhancing creativity allowing them to freely express themselves through their body, transmitting emotions, moods, feelings and above all, can develop their learning by playing. To diagnose how this process can be affected by inadequate strategies that the teacher does not achieve the goal that in every field of development is required to reach and not reach a significant situation has been the greatest achievement of research.